Early History of Puputan Bayu War and Petilasan Prabu Tawang Alun - Deanisha Eka Safitri; Nanda Abdul Majid; Feny Oktavia; Rizky Maulana; Tri Devi Ulil Azmi; Rino Dwi Saputra; Mahfud, Mahfud (SINGOSARI: Jurnal Perkumpulan Prodi Pendidikan Sejarah Se-Indonesia (P3SI) Wilayah Jawa Timur, 2024)
The village where Rowo Bayu Banyuwangi is composed of village area, land, agriculture and florest. The Village is know as location of Bayu puputan war that took place between prince Jagapati of the Kingdom of Blambangan and the VOC in 1773. The purpose of the existence of the Tawang Alun Prabu petition. The results who wass the king who led the Kedawung Kingdom who eventually decided his throne from his sister who wanted to rule the Kingdom And left the Kingdom who went to Rowo Bayu to be seated. The writing of this article uses a descriptive method based on data extraction through interviews and also through the study of the Library from several written sources.